NICKEL-METAL HYDRIDE BATTERY - SAIDA, Jun; SASAKI, Hiroyuki; YASUDA, Shuichi; KAWAI, Tomoyuki; NIWA, Junichi; OKANISHI, Takeo (2018)
Provided is a nickel-metal hydride battery which can be prevented from the generation of oxygen. A nickel-metal hydride battery characterized by being provided with: a positive electrode containing Y2O3 and/or M2WO4 (wherein M represents an alkali metal); and an electrolytic solution containing an alkali metal halide and an alkali metal hydroxide. L'invention fournit une batterie au nickel et hydrure métallique permettant d'inhiber l'apparition d'un oxygène. Cette batterie au nickel et hydrure métallique est caractéristique en ce qu'elle comporte : une électrode positive comprenant Ｙ2Ｏ3 et/ou Ｍ2ＷＯ4 (M représente un métal alcalin) ; et une solution électrolytique comprenant un halogénure de métal alcalin et un hydroxyde de métal alcalin. 酸素発生を抑制し得るニッケル金属水素化物電池を提供する。　Ｙ2Ｏ3及び／又はＭ2ＷＯ4（Ｍはアルカリ金属）を含有する正極と、　アルカリ金属ハロゲン化物とアルカリ金属水酸化物とを含有する電解液と、 を具備することを特徴とするニッケル金属水素化物電池。